2000
DOI: 10.1097/00000658-200007000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hematogenic Tumor Cell Dissemination in Patients Undergoing Resection of Liver Metastases of Colorectal Cancer

Abstract: ObjectiveTo determine the extent of pre-and intraoperative hematogenic tumor cell dissemination in patients undergoing liver resection for metastatic colorectal cancer. Summary Background DataFor patients with hepatic metastases of colorectal cancer, liver resection is the only potentially curative therapy. However, 38% to 53% of patients develop extrahepatic tumor recurrence, probably caused by tumor cells disseminated before or during surgery not detected by current staging systems. MethodsBlood samples harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1
11

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 41 publications
2
80
1
11
Order By: Relevance
“…The most extensive studies were performed by Weitz et al using RT-PCR for the detection of CK-20 transcripts in blood, BM and lymph nodes of patients undergoing surgery of colorectal tumors, as well as resection of liver metastases of colorectal cancer (7,9,10). By analyzing apical lymph nodes, they demonstrated that lymphogenic tumor cell dissemination is a common and frequent event in colorectal cancer preceding hematogenic tumor cell dissemination (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most extensive studies were performed by Weitz et al using RT-PCR for the detection of CK-20 transcripts in blood, BM and lymph nodes of patients undergoing surgery of colorectal tumors, as well as resection of liver metastases of colorectal cancer (7,9,10). By analyzing apical lymph nodes, they demonstrated that lymphogenic tumor cell dissemination is a common and frequent event in colorectal cancer preceding hematogenic tumor cell dissemination (7).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these patients have a high risk for extrahepatic tumor recurrence as a result of tumor cell dissemination during surgery, most likely caused by mechanical alteration of liver tumors located adjacent to the liver vein. Weitz et al demonstrated that CK-20 RT-PCR transcripts were significantly more often detected in blood samples taken from the central vein during surgery than before and after surgery of liver metastases of colorectal patients, suggesting that liver resection carries an increased risk for intraoperative tumor cell dissemination (10).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 It is in this population that prognostic markers may identify a subgroup of patients who are at a higher risk for disease relapse and who may also benefit from adjuvant therapy, especially from antitumoral agents with low systemic toxicity such as monoclonal antibodies, which have also proven to be effective against dormant tumor cells. 6,7 In this regard, there are several studies that have demonstrated that tumor cell detection is clearly related to an early relapse and decreased survival of the respective patients. 6,7,12,13 This new prognostic factor may change the surgical management of patients with colorectal liver metastases and may help to individualize the treatment of these patients with systemic or regional chemotherapy.…”
Section: Prognostic Factors and Management Of Colorectal Cancermentioning
confidence: 99%
“…The detection of disseminated tumor cells could help to identify a subgroup of patients at risk for disease relapse that could benefit from adjuvant therapy. 6,7 In this context, flow cytometry is one of the methods used to identify subgroups at risk for disease relapse. Flow cytometry allows an accurate quantification of cells and at the same time a multi-parameter characterization of each cell present in the blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 These studies are likely to be relevant for the implantation of tumor cells that are shed into the blood circulation during surgical manipulation. 11 However, in the majority of patients undergoing liver surgery, microscopic tumor cell deposits are already present at the time of surgery, and their detection in the liver parenchyma is associated with tumor recurrence and poor life expectancy. 12,13 At present, it is unknown how I/R in general, and vascular clamping in particular, affects the behavior of these micrometastases.…”
mentioning
confidence: 99%